Pendampingan Budidaya Lebah Klanceng, untuk mendukung Ekowisata Gunung Tirah Di Desa Gempolan, Kerjo Karanganyar - SUPRIYADI DARSOWIYONO; Purwanto Purwanto; Rosariastuti MMAR; Hartati S; Masyithoh G; Nufus M (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
ABSTRACT The Sebelas Maret University (UNS) Surakarta Forest Management Study Program has the obligation to assist the Forest Farmers Group (KTH) located in Karanganyar Regency. In the Semang hamlet, Gempolan Village, Kerjo Karanganyar sub-district, is blessed with the potential for natural resources and natural panoramas that should be developed based on ecotourism. with the support of the Tani Maju Forest Farmers Group (KTH) so far it has utilized the potential of existing natural resources for the development of the Gunung Tirah ecotourism-based tourism industry. The community's efforts in developing Gunung Tirah tourism so far, namely the community has provided various facilities that can attract visitors. To add to the attraction of visitors, it is necessary to equip a clanceng beekeeping object by utilizing rubber plant flowers that are around Mount Tirah's tourist attraction. The purpose of the activity is Assistance in Klanceng Bee Cultivation, to support Ecotourism of Mount Tirah in Gempolan Village, Kerjo Karanganyar. The implementation of the activity uses the Participatory Rural Appraisal (PRA) approach, with an emphasis on community participation in clanceng bee cultivation, starting from planning, funding, scheduling, taking action, as well as monitoring and evaluating. This activity is expected to attract visitors to Mount Tirah tourism objects, and form Mitra Village as one of the higher education science-techno-park models. Keywords: KTH Semang Maju, Trigona bee, Community development, Gunung Tirah